2016
DOI: 10.2460/ajvr.77.9.1005
|View full text |Cite
|
Sign up to set email alerts
|

Phase I-II clinical trial of hyaluronan-cisplatin nanoconjugate in dogs with naturally occurring malignant tumors

Abstract: Objective To conduct an open label, multi-dose Phase I/II clinical study in spontaneous canine cancers and evaluate the pharmacokinetics, safety, and efficacy of the hyaluronan-based cisplatin formulation (HA-Pt). Animals 13 dogs with heterogeneous, naturally occurring cancers. Procedures The dogs received up to four injections of 10-30 mg/m2 HA-Pt into the tumor or peritumoral sub-mucosa at three-week intervals. Blood sample (2 mL) was collected from the jugular catheter at 0.5, 1, 2, 4, and 24 hours foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…In a Phase I pharmacokinetic and short-term tolerability study, HylaPlat has shown satisfactory tolerability and improved distribution along with sustained retention in tumor and draining lymphatics in dogs with spontaneous soft tissue sarcomas [ 2 ]. In a combined Phase I/II study in dogs with naturally occurring malignant oral and nasal SCC, 3 of 7 dogs (43%) that received low-diaqua formulations of HylaPlat demonstrated complete responses [ 3 ]. The newer lyophilized formulation in the present report appears to have improved stability and safety since the medication can be reconstituted in water just prior to administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a Phase I pharmacokinetic and short-term tolerability study, HylaPlat has shown satisfactory tolerability and improved distribution along with sustained retention in tumor and draining lymphatics in dogs with spontaneous soft tissue sarcomas [ 2 ]. In a combined Phase I/II study in dogs with naturally occurring malignant oral and nasal SCC, 3 of 7 dogs (43%) that received low-diaqua formulations of HylaPlat demonstrated complete responses [ 3 ]. The newer lyophilized formulation in the present report appears to have improved stability and safety since the medication can be reconstituted in water just prior to administration.…”
Section: Discussionmentioning
confidence: 99%
“…HylaPlat has improved pharmacokinetics and sustained retention compared to intravenous cisplatin in dogs [ 2 ]. It is effective against oral squamous cell carcinomas in dogs as demonstrated by our previous Phase I/II clinical study [ 3 ] as well as other canine clinical studies in the literature [ 4 , 5 ]. Previously, HylaPlat was formulated as a liquid based injectable that had a short shelf life.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, in a phase I clinical trial of sixteen dogs with spontaneous tumours, three dogs reached complete response (two had oral and one nasal planum squamous cell carcinoma) and three dogs had stable disease after intratumoral or peritumoral HA–Pt injections (10–30 mg/m 2 , 1–4 intratumoral or peritumoral injections at 3 week-intervals), which is better than previously reported studies of free cisplatin. Although the toxicity rate for this study was high (60%), the authors explained it as a result of poor compound purification prior to performing the trial, resulting in diaquated impurities [ 54 ]. Interestingly, no nephrotoxicity, the main adverse effect of cisplatin treatment, was noticed in any of the dogs tested.…”
Section: Polymer-based Nanoparticlesmentioning
confidence: 99%
“…This is opposed to liver damage, an extremely rare side effect of standard cisplatin treatment, which resulted following HA–Pt administration. Hepatotoxicity probably appeared due to the large size of polymer-based HA–Pt, which could not be cleared through the kidney, and the HA, which is normally metabolized in the liver, that was used as the DDS [ 54 ]. Based on these primary results, a clinical trial on intratumoral injections of HA–Pt was recently approved for the treatment of mouth cancers (melanoma and sarcoma) in dogs (study No.…”
Section: Polymer-based Nanoparticlesmentioning
confidence: 99%